Trends in daily observed temperature and precipitation extremes over three Ethiopian eco-environments - Mekasha, Aklilu; Tesfaye, Kinde; Duncan, Alan J. (Wiley, 2014)
Ethiopia has wide eco‐environmental diversity ranging from extreme heat at one of the lowest places in the world to one of the coolest summits in Africa. Associated with this environmental diversity and climate change, climatic extremes are expected to change over time and also vary across eco‐environments in the country. This study was conducted to examine the trends of past precipitation and temperature extremes over three eco‐environments in Ethiopia. The study involved analysis of 20 extreme indices computed from daily temperature and precipitation data spanning over 42 years (1967–2008). The climate data were obtained from 11 stations selected from three major eco‐environments (pastoral, agropastoral and highland). The results indicated positive trends for maximum value of the maximum temperature (TXx), warm days (TX90p), warm nights (TN90p) and warm spell duration indicators (WSDI) and negative trends for cool days (TX10p), cool nights (TN10p) and cold spell duration indicators (CSDI) in more than 8 of the 11 stations studied. However, most of the trends were not significant at many of the stations and the significant trends were not uniquely differentiated by eco‐environments. Unlike temperature extremes, precipitation extreme trends showed high variability among nearby stations within eco‐environments and were not significant at many of the stations studied. It is concluded that trends of temperature and precipitation extremes vary considerably among stations located within a given eco‐environment indicating that the response of local climate to global warming could be different in physiographically diverse regions.